Perkiraan Koefisien-koefisien Karakteristik Daerah Aliran Sungai Krengseng untuk Membangun Kurva-Durasi Debit - Sachro, Sri Sangkawati; Sugiyanto, Sugiyanto; Budieny, Hary (Department of Civil Engineering, Diponegoro University, 2013)
The flow-duration curve at a site is most useful tool for evaluating flows in water resources development projects. Flow-duration curves are based on cotinuous stream flow data, where stream flow meuserements are not available, precipitation and potensial evapotranspiration records can be used to calculate continuous flows. Calculation of monthly flows from meteorologic data are based on the water balance in watershed. The water balance equation is Precipitation – Actual evapotranspiration + Storage = Runoff. This calculation use coefficients that represent watershed characteristics, that will change from one watershed to another. The watershed characteristic coefficients changes will correlate with changes in vegetation, soils, and subsurface geology. This study is an attempt to estimate the watershed characteristic coefficients to calculate monthly streamflows in Krengseng River at Diponegoro Dam site. The watershed characteristic coefficients analysis using F.J.Mock Model and NRECA Model. Resuls of watershed characteristic coefficients analysis using F.J.Mock are, Expose surface, m = 50%, Soil moisture capacity, SMC = 200 mm, Infiltration factor, IF = 0.45, Recesion coeffisien, RC =0.70. Watershed characteristic coefficients using Model NRECA are, Index soil moisture capacity, Nominal:100+(0.25xmean annual precipitation), Base flow parameter, PSUB = 0.30 and Index groundwater storage, GWF=0.50.